Influences of Resistance versus Aerobic Exercise on Physiological and Physical Fitness Changes in Previously Inactive Men with Obesity: A Prospective, Single-Blinded Randomized Controlled Trial - Kim B (Dove Medical Press, 2020)
Bokun Kim,1 Seungyeol Kim2 1Faculty of Sports Health Care, Inje University, Gimhae, Gyeongsangnamdo, Republic of Korea; 2College of Arts and Sports, Dong-A University, Busan, Republic of KoreaCorrespondence: Seungyeol KimCollege of Arts and Sports, Dong-A University, 37 Nakdong-Daero 550beon-gil Saha-Gu, Busan 604-714, Republic of KoreaTel +82 10 8890 0643Email srkimjp@hanmail.netPurpose: The purpose of this study was to comparatively investigate changes in physiological and physical fitness in previously inactive men with obesity in response to aerobic exercise (AE) or resistance exercise (RE).Methods: A total of 27 inactive men with obesity, aged 34– 60 years, attended a 90-min AE or RE program 3 days/week for 12 weeks. The subjects underwent assessments of energy intake (by a 3-day weighted dietary record), body weight (by a digital scale), body composition (by whole-body dual-energy X-ray absorptiometry), VO2max (by a cycling ergometer), muscle strength (by a Biodex System 3 dynamometer) and blood analysis.Results: There were no significant interactions (P = 0.100∼ 0.730) among energy intake variables. RE led to decreased fat mass (− 4.39%, P < 0.05) and improved cardiorespiratory capacity (+11.66%, P < 0.05), as well as increases in lean mass (+2.12%, P < 0.01) and muscle strength variables (+8.41∼+11.00%, P < 0.01 for all), without significant weight change. Although AE induced decreases in fat mass (− 5.91%, P < 0.05) and weight (− 2.28%, P < 0.05) and improved cardiorespiratory capacity (+19.07%, P < 0.01), lean mass and muscle strength variables remained unchanged. RE showed a stronger positive influence than AE on lean mass (P = 0.003) and muscle strength variables (P = 0.001∼ 0.015), and RE and AE had similar influences on weight, fat mass, cardiorespiratory capacity and blood markers.Conclusion: It may be an efficient exercise regimen to perform RE first and then utilize AE to maintain the changes that occur in response to RE.Keywords: aerobic exercise, body composition, blood marker, cardiorespiratory capacity, obesity, muscle strength, resistance exercise, weight